Optimalisasi Learning Cycle 5E berbasis Computational Thinking Untuk Melatih Keterampilan Berpikir Kritis Materi Bentuk Molekul: Penelitian - Ega Silvia Lutviana; Muntholib; Dasianto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This material is abstract because it involves spatial concepts and three-dimensional molecular structures that cannot be observed directly. As a result, students have difficulty in imagining the shape of molecules and determining specifications with electron domain theory and bond angles. This study aims to train students' critical thinking skills so that it is hoped that it can improve students' cognitive abilities in the Molecular Form material through the application of the Learning Cycle 5E model by integrating Computational Thinking (CT). The research method used is classroom action research (CAR). The subjects in this study were students of class X-6 SMA Brawijaya Smart School in the 2024/2025 academic year. The instruments used were pretest and posttest in each cycle and checklist-based observation sheets. The data obtained were analyzed descriptively. Based on the results of observations from cycle I and cycle II, there was an increase in students' cognitive learning outcomes. The percentage of cognitive learning outcome completion was 21.87% and 90.63%. Based on these data, it can be concluded that through the application of the Learning Cycle 5E model by integrating the Computational Thinking approach and with the help of PhET Interactive Simulations media, it can train students' critical thinking skills in learning.